Association of balance control mechanisms with brain structural integrity in older adults with mild cognitive impairment. (13th July 2022) - Kannan, Lakshmi; Bhatt, Tanvi; Zhang, Aifeng; Ajilore, Olusola
Highlights: Structural brain integrity may influence balance control stability in older adults with mild cognitive impairment. Volitional and reactive balance control may share some common cortico-subcortical motor pathways and relay centers, and could be affected in older adults with mild cognitive impairment contributing to the increased fall risk. Abstract: Background: Older adults with mild cognitive impairment (OAwMCI) exhibit subtle balance control and gait deficits which are predominantly associated with structural brain pathologies such as impaired white matter integrity and reduced gray matter volume. However, the relationship between balance recovery mechanisms and neural substrates in OAwMCI remains unknown. This study thus aimed to explore the associations of volitional (self-initiated) and reactive balance (in response to an external perturbation) control with structural brain integrity. Methods: Ten OAwMCI (MoCA 18-25/30; greater than 55 years) were examined on the limits of stability test (volitional balance via Equitest), stance perturbation test (reactive balance via ActiveStep treadmill) and underwent magnetic resonance imaging. Forward movement (frequently performed functional activity of daily living) was quantified by maximum excursion (maximum ability to shift one's center of gravity toward the theoretical limit [MXE-%]) and directional control (amount of movement exhibited towards the target proportional to the movement away from the target [DCL-%]) on the limits of stability test. Slip-like (prevalent type of accidental falls) perturbations were quantified by postural stability (shortest distance of the COM motion state, i.e., its position and velocity, to the theoretical boundary) on the ActiveStep treadmill. White matter integrity was quantified by fractional anisotropy (FA, movement of water molecules directionality) and gray matter volume measured in mm 3 . Results: For volitional balance control, reduced forward MXE was significantly ( p < 0.05 ) associated with lower FA in left ( R 2  = 0.56 ) and right ( R 2  = 0.60 ) corticospinal tract, left ( R 2  = 0.49 ) and right ( R 2  = 0.51 ) corticothalamic tract, left ( R 2  = 0.70 ) and right ( R 2  = 0.57 ) frontopontine tract, right ( R 2  = 0.67 ) cingulum, anterior commissure ( R 2  = 0.82 ), and corpus callosum ( R 2  = 0.62 ). Reduced forward DCL was significantly ( p < 0.05 ) associated with reduced gray matter volume in the left ( R 2  = 0.75 ) and right ( R 2  = 0.81 ) cerebellum, brainstem ( R 2  = 0.64 ), right ( R 2  = 0.49 ) thalamus. For reactive balance control, reduced postural stability ( p < 0.05 ) was significantly associated with reduced FA in the left ( R 2  = 0.75 ) and right ( R 2  = 0.64 ) corticospinal tract, left ( R 2  = 0.67 ) and right ( R 2  = 0.65 ) frontopontine tract. Reduced postural stability was significantly ( p < 0.05 ) associated with reduced gray matter volume in the brainstem ( R 2  = 0.72 ) and right cerebellum ( R 2  = 0.70 ). Conclusion: Our results indicate that structural brain integrity influences stability control in OAwMCI for both volitional and reactive balance tasks, which may share some common cortico-subcortical motor pathways and relay centers. Results also show that the integrity of descending pathways from cortical attentional centers could influence stability control for both tasks.